(untitled) (Orinoquia, 2009)
ABSTRACT: The results of the recent research group classification during the past Colciencias meeting for such purpose in 2008 revealed a significant increase in institutional research capacity, rising from 2 to 11 groups recognised by the Universidad de los Llanos and another 10 belonging to other institutions.